Perceived Racial Discrimination in the Pregnant African American Population: A Concept Analysis. (October 2021) - Mileski, Megan R.; Shirey, Maria R.; Patrician, Patricia A.; Childs, Gwendolyn
Abstract : African American women experience higher lifetime exposure to chronic stressors, such as perceived racial discrimination. Clearly defining perceived racial discrimination in the pregnant African American population has the potential to better explain the phenomenon and how it relates to adverse birth outcomes such as preterm birth. The purpose of this concept analysis is to more clearly define perceived racial discrimination in the pregnant African American population using Rodgers' evolutionary method. Defining the concept of interest has the potential to uncover modifiers that may help close the gap in the Black-White infant mortality rates in the United States.